2022
DOI: 10.36519/idcm.2022.110
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Severity and Mortality in COVID-19: A Retrospective Study from Batman, Turkey

Abstract: Objective: It is increasingly important to identify risk factors for COVID-19-associated mortality to provide access to early treatment. This study aimed to investigate the relationship between COVID-19 severity and laboratory data and demographic characteristics of hospitalized patients and to identify factors predicting mortality in COVID-19. Materials and Methods:The study is a retrospective and single-center study. Data of 1298 COVID-19 patients confirmed by a positive real-time polymerase chain reaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Severe disease and PCO2 were also correlated with the chance of death. In previous studies, it has been shown that other factors like comorbidities, obesity, D-dimer, low SpO2/FiO2 ratio, male gender, and higher age are associated with disease severity and mortality [ 68 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe disease and PCO2 were also correlated with the chance of death. In previous studies, it has been shown that other factors like comorbidities, obesity, D-dimer, low SpO2/FiO2 ratio, male gender, and higher age are associated with disease severity and mortality [ 68 70 ].…”
Section: Discussionmentioning
confidence: 99%